The Validity of Student Worksheets Based on Argument-Driven Inquiry (ADI) in Cell Structure and Plant Tissue Material to Train Critical Thinking Skill for Senior High School Students - Salsabela, Aulia Itsnaini; Puspitawati, Rinie Pratiwi (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2020)
Critical thinking skills is one of the 21st century competencies that students need to have in education. Therefore, teaching materials must be developed in learning process, one of them is student worksheets with Argument-Driven Inquiry (ADI) based. Argument-Driven Inquiry is an inquiry learning model that effective to improving the critical thinking skill students by argumentation skill. One of the materials apropriated with ADI model is the structure plant of cells and plant tissue. This study aimed to describe the validity and produce worksheets based on Argument-Driven Inquiry in structure of plant cells and plant tissue material to train critical thinking skill for senior high school students. The method used in this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The phase carried out only reached the stage of student worksheets development. Student worksheets development carried out in Biology Department, Faculty of Mathematics and Natural Sciences, Surabaya State University. The validity of student worksheets obtained from the validators using the validation sheet. The results showed that the worksheets was declaring to be very valid with an average score of 3.74. Based on the data obtained, it can be concluded that student worksheets developed declared feasible based on its validity and could be used in the learning process. Keywords: Student worksheets, validity, critical thinking skills, Argument-driven Inquiry (ADI), structure of cells and plant tissue